2009
DOI: 10.2174/092986609789839368
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Sequences Potentially Related to Resistance Response of Piper tuberculatum to Fusarium solani f. sp. piperis by Suppression Subtractive Hybridization

Abstract: Piper tuberculatum is an exotic Piper from the Amazon region that shows resistance to infection by Fusarium solani f. sp. piperis, causal agent of Fusarium disease in black pepper (Piper nigrum L.). In this work we aimed to study the interaction between P. tuberculatum and F. solani f. sp. piperis at a molecular level, using suppression subtractive hybridization to identify genes potentially related to Fusarium disease resistance. Comparative sequence analysis confirmed that clones isolated here show a high id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
9
0
2
Order By: Relevance
“…It is cultivated in Asian countries such as Malaysia, India, Indonesia, Thailand, Vietnam, China and Sri Lanka, in addition to Madagascar and Brazil [ 1 , 2 ]. In Brazil, the cultivation of P. nigrum started in the 17th century and since 1933, it has been economically explored by Japanese immigrants [ 3 ]. Pará state is the largest producer in Brazil, with about 90% of national production, representing the third largest production in the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is cultivated in Asian countries such as Malaysia, India, Indonesia, Thailand, Vietnam, China and Sri Lanka, in addition to Madagascar and Brazil [ 1 , 2 ]. In Brazil, the cultivation of P. nigrum started in the 17th century and since 1933, it has been economically explored by Japanese immigrants [ 3 ]. Pará state is the largest producer in Brazil, with about 90% of national production, representing the third largest production in the world.…”
Section: Introductionmentioning
confidence: 99%
“…piperis (Brazil) are the causative agents of root rot or Fusarium disease (fusariosis) to the crop of black pepper [ 6 ]. The first symptoms of fusariosis start at the roots or branches and promote falling leaves, root rot, and plant death [ 3 ]. Pathogens that cause wilting, such as Fusarium solani f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study by Schenk et al (2014) showed that N-acyl-homoserine lactone, a bacterial quorum-sensing molecule, was able to prime cell wall-related genes in Arabidopsis thaliana plants and, as a result, induce resistance to bacterial pathogens by way of cell wall reinforcement. Since we have identified sequences of P. tuberculatum that code for proteins potentially involved in the formation of structural barriers against F. solani f. sp piperis infection, including a putative cell wall hydroxyproline-rich glycoprotein (Nascimento et al, 2009); it is possible that the Pseudomonas bacteria isolated in the present study contribute to resistance to this fungus by similar mechanisms. However, further studies will elucidate the roles of Pt12 and Pt13 isolates in the physiology of P. tuberculatum.…”
Section: Endophytic Bacteria Of P Tuberculatum Are Associated With Pmentioning
confidence: 97%
“…On the other hand, in a compatible interaction a susceptible plant is infected by an adapted pathogen, inducing the development of disease, which commonly leads to death. Studies show that in some plants the defense reaction can be delayed or the pathogen can employ mechanisms to inhibit the defense (Bell et al 1986;Jakobek et al 1993;Alfano and Collmer 1996;Desender et al 2007;Rinaldi et al 2007) The identification of genes expressed during compatible and incompatible plant-pathogen interactions have contributed to understanding molecular mechanisms involved in plant response, and defense process (Fekete et al 2009;Nascimento et al 2009;Mukherjee et al 2009;Schlink 2010); furthermore, such genes have been employed successfully in the production of transgenic plants (Latha et al 2005;Zuo et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported by Nascimento et al (2009) revealed the identification of P. tuberculatum sequences coding for peroxidase and hydroxyproline-rich glycoprotein potentially involved in the formation of structural barriers against F. solani f. sp. piperis infection.…”
Section: Introductionmentioning
confidence: 99%